Síntese enzimática de ampicilina em reator integrado - Ferreira, Andrea Lopes de Oliveira (2004)
Enzymatic route to produce antibiotic acts in mild reaction conditions (aqueous medium, neutral pH and moderate temperatures). Furthermore it reduces the number of reaction steps and decreases the amount and toxicity of waste products per kilogram of antibiotic. The enzymatic synthesis of ampicillin from phenylglycine methyl ester (PGME) and 6-aminopenicillanic acid (6-APA) can be an attractive alternative, replacing the chemical route. The use of an immobilized enzyme to catalyze the synthesis is very important to reduce costs. Penicillin G acylase (PGA) [EC 3.5.1.11] from E. coli was immobilized on two supports (agarose gel and silica). This work undertakes an optimization study of the enzymatic synthesis of ampicillin, to find out optimized process conditions. Therefore, it was studied the influence of the following variables: pH, temperature, 6-APA initial concentration, buffer concentration and the presence of methanol. Response variables were productivity, selectivity and yield (based on 6- APA initial concentration). The assays were carried on accordind to factorial design 25. Temperature, pH, and 6-APA initial concentration influenced At synthesis of ampicillin from PGME and 6-APA, two other reactions compete with the synthesis reaction: hydrolysis of PGME (a parallel reaction) and hydrolysis of ampicillin (in series with the synthesis). The yield of the synthesis of ampicillin depend on the rates of three different reactions. The highest yield was achieved at 4ºC, pH 6.5, without methanol, and with low buffer concentration. The results also indicate that it is possible to work with this system at high productivities, and it still keeps high yields at 25ºC, without buffer, and pH 6.5. After the selection of reaction conditions (25ºC, pH 6.5), assays with PGA immobilized on silica carrier were realized. Convensional reactors may cause shearing on derivative enzyme-silica, which led using fixed-bed reactor. Mass transport parameters were estimated by fitting heterogeneous mathematical model to experimental data of catalytic bed with recirculation, running on transient state. Another used support on immobilized enzyme was agarose gel. Domain of experimental assays used in the neural network training and validation were initial substrate concentrations ranged from 50 to 250mM. A mechanistic model to represent the synthesis of ampicillin from PGME and 6-APA is a set of seriesparallel reactions (ampicillin and PGME hydrolysis are undesirable side reactions) would be too complex, with an intractable number of kinetic parameters. Simplified models could not represent all the experimental data, and a hybrid model was used. Neural networks were trained to predict reaction rates and used in the mass balance equations. A feedforward neural network, with one hidden layer was used. Results of the simulation were promising. The operational region that of high productivity and selectivity of antibiotic could be successfully mapped. An important aspect to improve the selectivity of ampicillin synthesis is to precipitate the antibiotic because the hydrolysis reaction would be decreasing. An approprieted biocatalyst which preventing the precipitation was developed, and used in a Taylor vortex reactor where shears are smaller. Synthesis assays using high substrate concentrations were performed in this reactor, occurring precipitate of antibiotic during reaction, to improve yield, selectivity, and productivity of this system.